Human-elephant Conflict in the Southern Western Ghats : a Case Study from the Peppara Wildlife Sanctuary, Kerala, India - Jayson, E. A.; Christopher, G. (Indian Forester, 2008)
Human-elephant conflict in Peppara Wildlife Sanctuary and adjacent areas was studied based on observational methods during the year 1993 to 1996 as a part of project studying the large mammals in the sanctuary. Peppara Wildlife Sanctuary, situated at an altitude ranging from 98 to 1594 m amsl in the southern Western Ghats, India has diverse habitats like tropical moist deciduous and evergreen forests and plantations. Elephants were located 73 times during the period of study and altogether 217 elephants were seen, the male to female ratio was 1 : 6 (N = 217). Mean herd size was 10 individuals per herd and maximum numbers was sighted in the moist deciduous forest followed by eucalypt plantation, swampy areas, semievergreen forest and evergreen forest. Plant species used as food by elephants was also recorded, when they were not involved in crop raiding. Major animals engaged in crop damage were wild boar and elephant. The animals involved in crop damage were mainly lone males, in the case of elephants and most of the raids were at night. It was observed that substantial amount of crop was damaged as compared to what was consumed by the animals. Coconut was mainly damaged by elephants and the damage was confined to the trees less than 20 years. Coconut trees less than 10 years were pushed down and the central rachis and shoots were consumed. Plantains were also attacked by elephants, the leaves were discarded and the central portion of the stem consumed. Elephant also destroyed paddy, rubber and pineapple by trampling. While damage by wild boar was recorded throughout the year, the attack from elephants was related to the species of crops cultivated. Besides crop damage instances, four human deaths were also recorded. Crop damage is linked to the cropping pattern and location of settlements and it is one of the problems, which severely affects the economic status of tribals.